Examining the role of key competences in firm performance. Issue 4 (11th December 2019) - Škrinjarić, Bruno; Domadenik, Polona
Abstract : Purpose: Industry 4.0 processes brought dramatic changes in skills and competences needed at the firm level. The purpose of this paper is: to identify and quantify key competences required for workers with economics-and-business background; to evaluate development level of those competences among the currently employed workforce; to investigate degree of match between required and currently developed competences; and finally to assess how this (mis)match translates to firm performance. Design/methodology/approach: This research is based on primary data, collected through questionnaires, and secondary data of firms' financial and structural characteristics. Key competences were estimated using factor analysis and were then used as covariates in explaining differences in firms' performance in both static and dynamic production function specifications using standard regression model, Heckman selection model and Arellano–Bond estimation. Findings: Results show that mismatches in competences basic algebra; collectedness, conflict resolution and presentation; and motivation and organization are all negatively associated in explaining the variation of firm performance, with motivation and organization having the most significant effect. Originality/value: This paper focuses on competence mismatch by including both sides of the labor market (employers and employees) in the analysis. This paper offers: a theoretical structure for understanding and investigating existing competence mismatches; a step-by-step industry-driven method for deriving key required competences, including an initial exploratory phase (combination of literature review, exploratory interviews and pilot study) followed by a descriptive and implementation phases (design, implementation and analysis of nationally representative survey); and finally, analysis phase (associating competence mismatches to firm performance).